1999
DOI: 10.1128/aem.65.3.1268-1279.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epichloë Endophytes In Planta by a Microsatellite-Based PCR Fingerprinting Assay with Automated Analysis

Abstract: Epichloë endophytes are a group of filamentous fungi that include both sexual (Epichloë) and asexual (Neotyphodium) species. As a group they are genetically diverse and form both antagonistic and mutualistic associations with temperate grasses. We report here on the development of a microsatellite-based PCR system for fingerprinting this group of fungi with template isolated from either culture or infected plant material. M13mp19 partial genomic libraries were constructed for size-fractionated genomic DNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 56 publications
1
100
1
Order By: Relevance
“…The markers have been shown to display high levels of cross-species transfer in in vitro-based studies, null alleles being less frequent than for genomic DNA-derived SSR markers (Moon et al, 2000(Moon et al, , 2004van Zijll de Jong et al, 2003). In contrast to some of the more commonly used methods, such as histological, serological and immunoblot detection methods (Belanger, 1996;Hiatt et al, 1999;Musgrave, 1984), SSR markers have been shown here, and in other studies, not only to detect endophyte but also to discriminate diff erent taxa and even strains of endophyte (Moon et al, 1999;van Zijll de Jong et al, 2003. This level of discrimination has not been reported for sequence tagged site markers (Dombrowski et al, 2006;Doss et al, 1998).…”
Section: Effi Ciency Of In Planta Endophyte Genotypingmentioning
confidence: 56%
See 3 more Smart Citations
“…The markers have been shown to display high levels of cross-species transfer in in vitro-based studies, null alleles being less frequent than for genomic DNA-derived SSR markers (Moon et al, 2000(Moon et al, , 2004van Zijll de Jong et al, 2003). In contrast to some of the more commonly used methods, such as histological, serological and immunoblot detection methods (Belanger, 1996;Hiatt et al, 1999;Musgrave, 1984), SSR markers have been shown here, and in other studies, not only to detect endophyte but also to discriminate diff erent taxa and even strains of endophyte (Moon et al, 1999;van Zijll de Jong et al, 2003. This level of discrimination has not been reported for sequence tagged site markers (Dombrowski et al, 2006;Doss et al, 1998).…”
Section: Effi Ciency Of In Planta Endophyte Genotypingmentioning
confidence: 56%
“…As for genomic DNA-derived SSR markers (Groppe and Boller, 1997;Moon et al, 1999), expressed sequence tag (EST)-derived SSR markers were highly eff ective for in planta endophyte detection. The effi ciency of marker conversion from in vitro to in planta-based detection was high (>80%), both for tillers and seeds.…”
Section: Effi Ciency Of In Planta Endophyte Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…All SSR primers were synthesised by Integrated DNA Technologies, Inc. (Coralville, IA). PCR using B10 and B11 was performed as described by Moon et al (1999), except that a 10 lL reaction volume was used. For all other SSRs, PCR amplifications were conducted in a 10 lL reaction volume as per Faville et al (2004) except that a final concentration of 2.5 mM magnesium chloride and 0.75 units of Platinum Taq DNA polymerase (Life Technologies, Carlsbad, CA) were used.…”
Section: Simple Sequence Repeat Analysis Of Endophyte Strainsmentioning
confidence: 99%